The effect of using helpful method according to some kinematic changes in shooting accuracy from the free aria in basket ball for the helds up players on the moving chairs - Khaled, Waled (Journal of Physical Education, 2011)
The thesis has contains five chapters: Chapter one (the research definition): This chapter has contains: the research introduction and its important ,the research aims ,research imposing ,research sphere(human sphere ,timely sphere ,place sphere). Chapter two (the similar and theorem studies): This chapter has contains: astriction ,basketball ,for the held up players ,the main skills in basketball on the moving chairs ,the helping devices ,the movement canalization. Chapter three (the research methodic and its median procedures): This chapter has contains: research approach , research society , research sample ,the devices of contains the information ,devices and articles that used , research median procedure ,the biomechanical analization by using computer soft ware and the statistical devices. Chapter for (show the results ,discussing it and analyzing it): This chapter has contains: shows the result of the biomechanical changes to do the shooting skills from the free aria ,discussing and analyzing it. Chapter five (conclusions and recommendations)